Visualisasi Rumah Gadang dalam Ekspresi Seni Lukis - Harissman Harissman; Suryanti Suryanti (PANGGUNG, 2019)
ABSTRACTThe purpose of this art creation is to transform the values of Rumah Gadang into painting. Rumah Gadang (Big House) is a traditional house of Minangkabau ethnic in West Sumatera Province of Indonesia. Rumah Gadang is built on the pillars made from the wood. It has a high and big hollow on the ground, and its taper roof is a special characteristic that makes it different from other ethnic houses in the areas across the equator. Rumah Gadang has various types and names based on its shape and size, which depend on the community or ethnic group that builds the house. Rumah Gadang Batingkek (a big attic house) accommodates the system of Koto Piliang group, while Gajah Maharam (Incubated Elephants) is an identity of Rumah Gadang of Bodi Caniago community. Both models of the traditional houses above have been known as the identity of a Minangkabau traditional house. Methods used for this artwork are exploration, planning, and implementation of the artwork. Before practising these methods, the data has been explored through library research, empirical research, and field research. Idioms of the traditional houses expressed in the language of painting as an expression of the Painters in communicating their concern of changing the functions and values of Rumah Gadang in Minangkabau society today. By expressing through painting, it is hoped it can give awareness to the people to preserve the traditional values of Rumah Gadang, and also the continuity of appreciation to the house.Keywords: Rumah Gadang, art painting, traditional values, expression of the artABSTRAKPenelitian dalam penciptaan ini bertujuan untuk mengaktualisasikan nilai-nilai Rumah Gadang ke dalam karya seni lukis. Rumah gadang merupakan rumah tradisional suku Minangkabau di Sumatera Barat. Rumah Gadang dibangun di atas tiang (panggung), mempunyai kolong yang tinggi, serta atapnya yang lancip, merupakan arsitektur yang khas yang berbeda dengan bangunan suku bangsa lain di daerah garis khatulistiwa. Rumah Gadang mempunyai nama dan jenis yang beraneka ragam menurut bentuk dan ukurannya, sesuai kaum atau suku yang membuatnya. Rumah Gadang Batingkek (rumah besar bertingkat) mengakomodasi sistem kelarasan Koto piliang, yang Rumah Gadangnya beranjuang, Gajah Maharam (gajah mengeram) mengidentitaskan Rumah Gadang kelarasan Bodi Caniago. Kedua model Rumah Gadang tersebut merupakan identitas bangunan etnis Minangkabau. Metode penelitian dilakukan dengan eksplorasi, perancangan, dan eksekusi dari perwujudan karya seni. Pada tahap sebelumnya, dilakukan beberapa tahapan, yaitu studi pustaka, studi empirik dan studi lapangan. Dari penelitian didapatkan kesimpulan bahwa Idiom-idiom tradisi Rumah Gadang yang diungkapkan dengan bahasa seni lukis merupakan media ekspresi pencipta untuk mengomunikasikan kegelisahannya mengenai perubahan dan pengikisan nilai yang terjadi di Rumah Gadang sesuai perubahan zaman. Dengan media ungkap bahasa visual ini diharapkan dapat memberi penyadaran akan pentingnya nilai tradisi dalam konteks Rumah Gadang, serta terus diapresiasi. Kata kunci: Rumah Gadang, seni lukis, nilai-nilai tradisi, ekspresi seni